G2019S LRRK2 Increases Stress Susceptibility Through Inhibition of DAF-16 Nuclear Translocation in a 14-3-3 Associated-Manner in Caenorhabditis elegans - Long, Simei; Guo, Wenyuan; Hu, Sophie; Su, Fengjuan; Zeng, Yixuan; Zeng, Jinsheng; Tan, Eng-King; Ross, Christopher A.; Pei, Zhong (Frontiers in Neuroscience, 2018)
Mutations in leucine-rich repeat kinase 2 (LRRK2) are common causes of familial Parkinson's disease (PD). Oxidative stress plays a key role in the pathogenesis of PD. Mutations in LRRK2 has been shown to increased susceptibility to oxidative stress. To explore the mechanisms underlying LRRK2 mutant's susceptibility to oxidative stress, we generated stable Caenorhabditis elegans (C. elegans) strains in which human LRRK2 proteins including wild type LRRK2 (WT), G2019S LRRK2 (G2019S) and G2019S-D1994A kinase dead LRRK2 (KD) were expressed in pan-neurons. Human 14-3-3 β was injected into LRRK2 transgenic worms to allow co-expression of 14-3-3 β and LRRK2 proteins. We found that G2019S transgenic worms had increased sensitivity to stress (heat and juglone treatment) and impaired stress-induced nuclear translocation of DAF-16. In addition, G2019S inhibited ftt2 (homolog 14-3-3 gene in C. elegans) knockdown-associated nuclear translocation of DAF-16. Comparably, over expression of human 14-3-3 β could attenuate G2019S-associated toxicity in response to stress and rescued G2019S-mediated inhibition of sod-3 and dod-3 expression. Taken together, our study provides evidence suggesting that 14-3-3 associated-inhibition of DAF-16 nuclear translocation could be a mechanism in G2019S LRRK2-induced oxidative stress and cellular toxicity. Our findings also highlight the potential of 14-3-3 proteins as neuroprotective targets in PD patients carrying LRRK2 mutations.